2008
DOI: 10.1097/nmd.0b013e31818ec7ee
|View full text |Cite
|
Sign up to set email alerts
|

Changing Profile of Abused Substances by Older Persons Entering Treatment

Abstract: This study evaluated whether there were increasing admissions for illicit drug abuse treatment among older persons from 1992 to 2005 in the United States and describes the characteristics, number, and type of substances most commonly abused in this population over this 14-year period. Analyses used public data files from the Treatment Episode Data Set, which tracks federally and state funded substance abuse treatment admissions. From 1992 to 2005, admissions for illicit drug abuse increased significantly; in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…In a study that compared samples collected with a 10-year interval, the men remained at a higher number in both samples (Sacco et al, 2013). Another study confirmed that admissions for drug or alcohol abuse, or a combination of the two; were predominantly men, although it should be noted that this percentage decreased between 1992 and 2005 for all drugs (Lofwall et al, 2008).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…In a study that compared samples collected with a 10-year interval, the men remained at a higher number in both samples (Sacco et al, 2013). Another study confirmed that admissions for drug or alcohol abuse, or a combination of the two; were predominantly men, although it should be noted that this percentage decreased between 1992 and 2005 for all drugs (Lofwall et al, 2008).…”
Section: Resultsmentioning
confidence: 61%
“…The Table 1 presents a synthesis of the information contained in the articles compiled in this review, whereby eight come from studies carried out in the United States (USA), two from the United Kingdom and one each from Brazil, Spain, and Australia. Of these, seven refer to data extracted from epidemiological studies, carried out to monitor the population (Armstrong, 2007;Blazer & Wu, 2009;Fahmy et al, 2012;Han et al, 2009;Horyniak et al, 2013;Lofwall et al, 2008;Sacco et al, 2013), based on large samples -between 3417 and 452,567 individuals. Four studies reported on data obtained through the application of questionnaires, evaluations or analysis of clinical histories of users of treatment services for problems related to drug use (Beynon et al, 2009;Lofwall et al, 2005;Pillon et al, 2010;Roibás et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations